2009
DOI: 10.5194/amt-2-573-2009
|View full text |Cite
|
Sign up to set email alerts
|

In-situ measurements of oxygen, carbon monoxide and greenhouse gases from Ochsenkopf tall tower in Germany

Abstract: In addition to the in-situ measurements, flask samples are taken at Ochsenkopf at approximately weekly intervals and are subsequently analysed for the mixing ratios of the same species, as well as H 2 , and the stable isotopes, δ 13 C, δ 18 O in CO 2 . The in-situ measurements of CO 2 and O 2 from 23 m show substantial diurnal variations that are modulated by biospheric fluxes, combustion of fossil fuels, and by diurnal changes in the planetary boundary layer height. Measurements from 163 m exhibit only very w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 52 publications
3
79
1
Order By: Relevance
“…The timing of the maximum of the seasonal variation is similar to CO 2 , and the mean peak-topeak amplitude of CO is 47.7 ppb averaged over the 2 years. Other tall tower stations in Europe reported much higher seasonal amplitudes between 75 and 130 ppb (Thompson et al, 2009;Vermeulen et al, 2011;Popa et al, 2010). Similar to CO 2 , some of the differences in the observed seasonal amplitudes might be related to data selection, and taking the daily means from the inter-quartile (25-75 %) range results in higher mean peak-to-peak amplitude of 54.5 ppb over the 2 years.…”
Section: Seasonal Variations and Annual Growth Ratementioning
confidence: 91%
See 3 more Smart Citations
“…The timing of the maximum of the seasonal variation is similar to CO 2 , and the mean peak-topeak amplitude of CO is 47.7 ppb averaged over the 2 years. Other tall tower stations in Europe reported much higher seasonal amplitudes between 75 and 130 ppb (Thompson et al, 2009;Vermeulen et al, 2011;Popa et al, 2010). Similar to CO 2 , some of the differences in the observed seasonal amplitudes might be related to data selection, and taking the daily means from the inter-quartile (25-75 %) range results in higher mean peak-to-peak amplitude of 54.5 ppb over the 2 years.…”
Section: Seasonal Variations and Annual Growth Ratementioning
confidence: 91%
“…Therefore, seasonal amplitudes for CH 4 were not calculated. In contrast to Beromünster, other tall tower stations in Europe (Thompson et al, 2009;Popa et al, 2010;Schmidt et al, 2014;Vermeulen et al, 2011) have reported more pronounced seasonal amplitudes between 35 and 70 ppb.…”
Section: Seasonal Variations and Annual Growth Ratementioning
confidence: 93%
See 2 more Smart Citations
“…The DFCA measures the O 2 mole fraction directly in dry air through an electrochemical method (Thompson et al, 2007(Thompson et al, , 2009Stephens et al, 2007). There are two sensors in the device, each containing an anode, cathode, and weak acid electrolyte.…”
Section: Atmospheric Oxygen Measurementsmentioning
confidence: 99%